Improvement of the aerodynamic performance of the Mataram University electric vehicle prototype - S. Suryadi; H.S. Tira; I.G.N.K. Yudhyadi (Universitas Mataram, 2026)
The number of motor vehicles worldwide increases every year, leading to higher pollution levels. To address this issue, various efforts have been made, one of which is improving vehicle design to enhance aerodynamics. This study aims to analyze the improvement in aerodynamic performance of the Mataram University prototype electric vehicle design. The computational fluid dynamics method was employed to achieve this objective. In this study, velocity variations of 10.48 m/s, 14.65 m/s, 18.82 m/s, 22.98 m/s, and 27.15 m/s were used. The results indicate an improvement in aerodynamics, as evidenced by a 5.682% reduction in the average drag coefficient compared to the initial design (2023). This reduction in drag coefficient signifies an enhancement in the vehicle’s aerodynamic efficiency, which positively impacts overall efficiency and reduces energy consumption.